PENDAMPINGAN KORBAN KEKERASAN SEKSUAL TERHADAP ANAK MELALUI PENDEKATAN PEKERJAAN SOSIAL - Sopi Nurhikmah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2018)
Sexual abuse of children is still a high case, in which governments, communities and families as the first in the child's education are concerned. Cases of child sexual abuse not only occur outside the ward but also occur within the family. In solving cases of child sexual abuse, there needs to be a chaperone. Chaperones are social workers who play a part in restoring the social functions of sexually abused children. The methods used in this writing are the use of library study methods by reviewing and analyzing books, journals, magazines, research results (thesis, thesis and accompanied) and other appropriate resources (Internet, newspapers, etc) as data sources. The results of this study include the limited treatment of child sexual abuse, the widespread content of pornography, the lack of punishment for abusers of child sexual abuse and a lack of understanding of parents' sexual abuse of children. Social workers as chaperones play a major role in the treatment of children who are victims of sexual abuse.